Whole gland versus partial gland ablation in patients with localized prostate cancer treated by high-intensity focused ultrasound ablation - Hae Sung Lee; Sang Hun Song; Hakmin Lee; Sung Kyu Hong (Prostate International)
Background: Focal therapy is considered one of the treatment options for localized prostate cancer (PCa), particularly for low or very-low-risk patients. In this study, we compared the mid-term oncological outcomes in localized PCa patients treated with high-intensity focused ultrasound (HIFU). Methods: We retrospectively analyzed 237 patients who underwent HIFU for localized PCa. Patients were divided into two groups based on ablation type: whole gland ablation (WGA) and partial gland ablation (PGA). Follow-up biopsies were performed after one year postoperatively, and the oncological outcomes were compared between the groups. Results: Among the total of 237 patients, 54 subjects were treated by WGA and 183 subjects by PGA. After one year postoperatively, follow-up biopsies were conducted on 199 patients, revealing residual cancer in 21.4% of WGA group and 15.3% of PGA group. Additionally, clinically significant (CS) cancer was observed in 14.3% of WGA group and 8.3% of PGA group. Survival analyses revealed significantly longer failure-free (P < 0.001) and salvage-free survival (P < 0.001) in WGA group than in PGA group. Similarly, in the intermediate—high risk group, WGA group exhibited longer failure-free (P = 0.005) and salvage-free survival (P < 0.001). Conclusion: HIFU was performed with acceptable oncological outcomes in localized PCa. Despite higher proportion of high-risk patients in WGA group, WGA was associated with significantly better failure-free survival and salvage-free survival. Further prospective and multi-center studies are warranted.